The value of biodiversity - Alho,CJR. (2008)
In addition to its intrinsic value (nature working as it is; species are the product of a long history of continuing evolution by means of ecological processes, and so they have the right to continued existence), biodiversity also plays a fundamental role as ecosystem services in the maintenance of natural ecological processes. The economic or utilitarian values of biodiversity rely upon the dependence of man on biodiversity; products that nature can provide: wood, food, fibers to make paper, resins, chemical organic products, genes as well as knowledge for biotechnology, including medicine and cosmetic sub-products. It also encompasses ecosystem services, such as climate regulation, reproductive and feeding habitats for commercial fish, some organisms that can create soil fertility through complex cycles and interactions, such as earthworms, termites and bacteria, in addition to fungi responsible for cycling nutrients like nitrogen, phosphorus and sulfur and making them available to plant absorption. These services are the benefits that people indirectly receive from natural ecosystem functions (air quality maintenance, regional climate, water quality, nutrient cycling, reproductive habitats of commercial fish, etc.) with their related economic values.